Combined Spinal-Epidural Anesthesia with Isobaric Ropivacaine 0.375% for Inguinal Hernia Surgery in a Heart Failure Patient with Ejection Fraction of 36% - Rayyan, Muhammad Isra Rafidin; Ghiffari, Salman Sultan; Hariyanto, Achmad; Winarso, Achmad Wahib Wahju; Darmawan, Haris; Fardhani, Ichlasul Mahdi (Indonesian Journal of Anesthesiology and Reanimation, 2024)
Introduction: Heart failure is a condition caused by myocardial abnormalities that interfere with the fulfillment of the body's metabolism. It is one of the primary causes of high perioperative morbidity and mortality rates, and its management presents a challenge to anesthesiologists. Objective: To demonstrate combined spinal-epidural anesthesia with isobaric ropivacaine 0.375% for inguinal hernia repair surgery in a heart failure patient with an ejection fraction of 36%. Case Report: A 53-year-old man presented with a complaint of a lump on his left groin accompanied by pain with a visual analog scale (VAS) pain score of 3/10 three days before admission. The patient was also known to often complain of shortness of breath and chest palpitations when lying down at night and during strenuous activity. Based on the examination, the patient was then diagnosed with reducible left lateral inguinal hernia and heart failure with LVEF 36%. Subsequently, the patient was scheduled for elective herniotomy-hernioraphy surgery under low-dose combined spinal-epidural anesthesia. Spinal anesthesia was performed with isobaric ropivacaine 0.375% and fentanyl 25 Î¼g in a total volume of 3.5 ml at the L3-L4 intervertebral space. Epidural anesthesia was performed with isobaric ropivacaine 0.375% and fentanyl 25 Î¼g in a total volume of 8 ml at the L2-L3 intervertebral space. After 10 minutes, the sensory block reached the T6 level, but the motor block was only partial (Bromage 1). A continuous infusion of isobaric ropivacaine 0.1875% 1 ml/hour was administered through the epidural catheter to control postoperative pain. During surgery and hospitalization, the patient's hemodynamic condition remained stable. Conclusion: Combined spinal-epidural anesthesia with isobaric ropivacaine 0.375% can provide adequate anesthesia with relatively stable hemodynamics, thus making it safe for inguinal hernia repair surgery in heart failure patients with reduced ejection fraction.